From "Here" to Eternity. Space-time singularities between literature, graphic novel and cinema (Comparatismi, 2025)
By reconciling the narrator and the reader-spectator’s opposite desires to run to the end of the story and to pause in the middle, to conclude and repeat, a literary, graphic or audiovisual narrative is a manifestation of “the internal logic of the discourse of mortality” (P. Brooks). A “narrative is significant to the extent that it draws the traits of temporal experience” (P. Ricœur), elaborating a discourse capable to exorcise the great human fears and sufferings: the senselessness of time, the prison of time, the loss of time, the end of time. The essay tests Ricœur’s theorem by analyzing Here, a paradoxical graphic story published by Richard McGuire in 1989 (as a comic strip) and then in 2014 (as a graphic novel), adapted for the big screen by Robert Zemeckis in 2024.